Vegetation Analysis of the Secondary Forest Area of ​​Mount Merapi National Park - Haryadi Haryadi; Sunarto Sunarto; Sugiyarto Sugiyarto (Jurnal Biodjati, 2019)
Mount Merapi National Park (MMNP) is a natural con-servation area with the main function of preserving the diversity of plants, animals and their ecosystems. In 2010, Mount Merapi suffered a large eruption which caused damage to the forest ecosystem inside. One of the locations that suffered severe damage was at Cangkrin-gan Resort. After the eruption, the affected vegetation began to grow again. The purpose of this study is to monitor and determine the di-versity of secondary forest plants in the MMNP area. The method used was a method of path and use a point-intercept transect as the sam-pling unit. The results showed that after the eruption, the Acacia de-curens dominated at each level starting from sapling, poles and trees. Based on the results of the study showed that the eruption of Mount Merapi that occurred in 2010 resulted in a change in vegetation struc-ture in the area with the Shannon-Weiner diversity index which is still low, amounting to 1.86 for seedling, 1.32 for the sapling and 0.22 for poles. At the tree level 100% is still dominated by Acacia decurens.